Using Virtual Reality as Learning Tools on Chemistry: Advantages and Challenges - Sari, Indah; Sinaga, Parlindungan; Hernani, Hernani; Mudzakir, Ahmad; Santria, Anas (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2023)
This research aims to elucidate the potential benefits and inherent challenges of employing Virtual Reality (VR) technology as an instructional tool in contemporary educational settings. With an emphasis on understanding teachers' perceptions, the study investigates the difficulties faced during traditional oral teaching and the potential advantages that VR-based pedagogy may bring to the educational environment. The participants of this empirical investigation included 20 educators (11 males and 9 females), who provided their insight on a set of 15 questions specifically designed and later analyzed via Rasch measurement. The Rasch model's assessment provided comprehensive insight into the teaching difficulties experienced by educators and the potential benefits accrued from the application of VR as a teaching aid. The findings indicate that the majority of educators face challenges while instructing through oral methodologies without appropriate pedagogical tools. Conversely, the integration of VR in teaching methods was found to foster students' knowledge acquisition, comprehension, and application in novel situations, augmenting their analytical and evaluative capabilities. VR application was also found to bolster student engagement, motivation, and attention in the learning process. However, despite these promising findings, several obstacles were identified, most notably the cost of VR technology and the requisite technical skills needed for its implementation by educators. The results of this study bear significant implications for future research, particularly as a teaching tool in chemistry. It also prompts a discussion on educators' capacity-building to seamlessly integrate VR technology into existing teaching methodologies.